Circular Economy Approach in Organic Fertilizer Production from Agricultural by-Products in Ba Vi District, Hanoi - Thi Phuong, Tran; Anh Le, Hoang; Van Thanh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 4DO - 10.25073/2588-1094/vnuees.4864, 2022)
Abstract: Ba Vi is one of the districts with huge agricultural production activities of Hanoi. Besides the main agricultural products supplied to the market, agricultural activities in Ba Vi also generate a large amount of by-products which are being wasted. In recent times, the model of using two main sources of cow manure and rice straw after harvest to produce organic fertilizer has opened a new direction for local economic development, taking advantage of agricultural by-products and solving many related environmental problems, such as greenhouse effect, pollutants emission by rice straw burning. This study aims to evaluate the efficiency as well as the accessibility to the circular economy of the organic fertilizer production model in Van Hoa commune, Ba Vi, Hanoi. The results show that organic fertilizer meets the standards with the incubation time of biological products in the range of 60-75; pH around 7.1; humidity less than 35%; The organic content is about 37.24 g/kg of manure. At peak times, each month this model is capable of handling more than 150 tons of agricultural by-products, creating jobs for 7-10 workers. The development of this organic production method has reduced the amount of straw burned on the field by 8.4%, treated 20.5% of livestock waste in the district, solved the difficult problem of inorganic fertilizers, and increased the level of waste use, which brings circular economy concept into practice.